Comparing the Apple iPad and non-Apple camp tablet PCs: a multicriteria decision analysis - Tsai, Pei-Hsuan; Chang, Shun-Chiao (Technological and Economic Development of Economy, 2014)
This study mainly evaluates the performances of Tablet PCs such as the Apple iPad based on a benefits, opportunity, costs, and risks (BOCR) conceptual framework with qualitative and quantitative criteria. We apply four methods, namely, the multiple-criteria decision-making (MCDM) tools (grey relational analysis (GRA), the technique for order performance by similarity to ideal solution (TOPSIS), the VlseKriterijumska Optimizacija I Kompromisno (VIKOR) method, and fuzzy approach) to evaluate and select the tablet PCs’ rankings and then construct a tablet PCs evaluation performance model under an analytic hierarchy process (AHP). The empirical results reveal that a firm's revenue growth, capacity for profitability, product design and product function are highly important evaluation indexes. This indicates that Tablet PC companies should channel more efforts into their product innovation for creating revenue growth and maintaining customer loyalty. Finally, fuzzy AHP also leads to the same findings.